Resolving sovereign debt crises: The role of political risk - Christoph Trebesch (Kiel Institute for the World Economy (IfW), 2018)
Sovereign defaults are bad news for investors and debtor countries, in particular if a default becomes messy and protracted. Why are some debt crises resolved quickly, in a matter of months, while others take many years to settle? This paper studies the duration of sovereign debt crises based on a new dataset and case study archive on debt renegotiations between governments and foreign banks and bondholders. Using Cox proportional hazard models, I find that domestic political instability ('political risk') is a significant predictor of negotiation delays, after controlling for macroeconomic conditions. Government crises, resignations, and street protests are particularly disruptive for a quick settlement process. Overall, the evidence suggests that debtor countries often lack the political ability to resolve a debt crisis. Governments in turmoil are unlikely to exit a default quickly.
Keywords: F34; F51; H63; 330; Sovereign Default; Crisis Resolution; Political Economy